2016
DOI: 10.1007/s40259-016-0175-4
|View full text |Cite
|
Sign up to set email alerts
|

How did the Introduction of Biosimilar Filgrastim Influence the Prescribing Pattern of Granulocyte Colony-Stimulating Factors? Results from a Multicentre, Population-Based Study, from Five Italian Centres in the Years 2009–2014

Abstract: Heterogeneity in the use of G-CSF and, in particular, biosimilar filgrastim across different Italian centres was observed, probably due to different regional healthcare policy interventions. During the first year of treatment, switching between different G-CSFs was frequent. Considering the impact of biological drugs on pharmaceutical expenses, it is necessary to harmonize healthcare policies promoting the use of biological drugs with the lowest cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…While not the focus of the current review, changing from one originator biologic to another is relatively common in clinical practice, most likely because of inefficacy or intolerability issues with the initial treatment [112, 113]. It is important to note, however, that this scenario is very different from switching between an originator biologic and its biosimilar or between different biosimilars of the same biologic: for example, two originator biologics targeting a given molecule may bind different epitopes, whereas a biologic and its biosimilar or two biosimilars of the same biologic should bind the same epitope.…”
Section: Discussionmentioning
confidence: 99%
“…While not the focus of the current review, changing from one originator biologic to another is relatively common in clinical practice, most likely because of inefficacy or intolerability issues with the initial treatment [112, 113]. It is important to note, however, that this scenario is very different from switching between an originator biologic and its biosimilar or between different biosimilars of the same biologic: for example, two originator biologics targeting a given molecule may bind different epitopes, whereas a biologic and its biosimilar or two biosimilars of the same biologic should bind the same epitope.…”
Section: Discussionmentioning
confidence: 99%
“…A recent drug-utilization study [20] found that filgrastim biosimilar use reached >60% in 2014 but varied widely between five Italian regions in which different policies were implemented between 2009 and 2014. Moreover, the study highlighted a switch rate of >20% between different G-CSFs during the first year of treatment, mainly across G-CSF originators (involving the filgrastim originator, lenograstim and pegfilgrastim).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, several regional provisions related to biosimilars regulate biologic prescription and expenditure targets. For example, (1) in the Campania and Umbria regions, the main objective is to achieve a biosimilar utilization rate at least equal to the number of naïve patients, whereas in the Veneto region, the dispensed packages of biosimilars must constitute at least 60% of all dispensed packages of G-CSF, EPO, or hGH; (2) in Sicily, Veneto, Campania, and Tuscany, drug-naïve patients must be treated with cheaper biosimilars, and when patients are switched, the lower cost medicine should be chosen; any deviations from these rules should be justified by the prescriber [57][58][59][60]. In Sweden, county councils set quotas and target budgets for hospitals, applicable to various therapeutic classes, including biosimilars.…”
Section: Demand-side Policies For Biosimilarsmentioning
confidence: 99%
“…Germany, Italy [58,59], and Belgium) or potential financial rewards for physicians who meet their targets (e.g. Italy [6], Sweden, some Spanish regions, and the UK [63,64]).…”
Section: Demand-side Policies For Biosimilarsmentioning
confidence: 99%
See 1 more Smart Citation